P7.2 VERY EARLY CLINICAL VASCULAR AND HEART MARKERS OF NEWLY RECOGNIZED HYPERTENSION IN MIDDLE AGE ADULTS - Olga Siga* (Artery Research, 2015)
The aim of this study was to evaluate vascular and echocardiographic markers of hypertension (HT) in subjects with newly diagnosed HT before treatment started. We studied 32 patients with newly diagnosed HT without pharmacological therapy (HT group) and 31 healthy ones (control group). ABPM were performed to exclude or confirm HT. Cardiovascular risk factors and pulse wave velocity (PWV) were assessed. Measurements of left ventricle, size of left atrium and parameters of diastolic function of left ventricle were measured using echocardiography. The student’s T-test, U Mann-Whitney and Chi2 tests were used to compare differences between groups. There were no significant differences in cardiovascular risk factors (sex, age, total cholesterol level, HbA1c) between groups with exception of BMI (p<0,05). We observed significant differences between HT group and control group in PWV, LVMI, LAVI, IVSd, LVIDd, LVPWd, E/A, E/E′, although there were no such differences in IVRT, DcT and E′.